Asthma and Pregnancy – Comorbid and Coexisting - González Díaz, Sandra Nora; Gallego Corella, Claudia Ivonne; Galindo Rodríguez, Gabriela; Leal Villarreal, Lucía; Arias Cruz, Alfredo; Buenfil López, José Antonio (Boal, 2012)
Asthma is considered the most common serious medical problem that could complicate pregnancy. During pregnancy the severity of asthma often changes, hence the patients need close follow up and monitoring exacerbations.